EVALUATION OF SOCIAL SECURITY OF BPJS KESEHATAN PROGRAM - Danial Thaib , Abdul Wahab Samad (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
This study aims to evaluate the implementation of social security of BPJS Kesehatan program which is provided to participants for non-contributory modality (PBI), contributory modality (non-PBI) for salaried workers, non-salaried workers and non-employees. This study measures the targets set by the achievements of the social security of BPJS Kesehatan program using the discrepancy evaluation model method. The evaluation of achievement of social security of BPJS Kesehatan program is to carrieout through the design, installation, process and results of the implementation of the social health insurance program on aspects of contributions and health services at primary care facilities and hospital facilities. The results show that the social security of BPJS Kesehatanprogram for the participants non-contributory modality (PBI), contributory modality (non-PBI) for salaried workers, non-salaried workers and non-employees still need to be increased for further to achieve universal and comprehensive health insurance coverage.